Pengembangan Media Poster Muatan PPKN Materi Pancasila Kelas IV - Nurul Raihan Fauziah; Nurul Kemala Dewi; Ilham Syahrul Jiwandono (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Learning media has a very important role in learning, learning media is also one part of the use of technology. Teachers and students are required to have skills in the use of science and technology. This study aims to produce a product and determine the feasibility, attractiveness, and how to make poster media that has been developed. The type of research used is R&D (Research and Development) research using the ADDIE research model (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation). This study uses qualitative and quantitative data with data collection techniques using documentation and questionnaires. The subjects of this study were 6 to 12 fourth grade students at SDN 27 Ampenan and the object of this research was the poster media of Pancasila and Citizenship Education content material Pancasila theme 4 sub-themes 1,2, and 3. The results of the research from material expert validators showed that the material on the poster media got very decent criteria with a score of 83%, from media expert validators showed that the media on the posters got very decent criteria with a score of 88%, the assessment of 6 students in the small group trial of poster media got interesting criteria with a score of 96%, and 12 students in the large group trial of poster media received attractive criteria with a score of 97%. The poster media for Pancasila and Citizenship Education theme 4 sub-themes 1,2, and 3 received an average of very decent criteria so that the poster media that had been developed could be used in schools without any material or visual revisions.